2004
DOI: 10.1002/macp.200400213
|View full text |Cite
|
Sign up to set email alerts
|

Surface Functionalized ZnO Particles Designed for the Use in Transparent Nanocomposites

Abstract: Summary: We present a new method for preparing a nanocomposite containing highly dispersed ZnO nanoparticles. The essence of this approach is the formation of surface modified inorganic particles and their homogeneous incorporation into a polymeric matrix. Therefore, an inverse emulsion of an inorganic salt, for example, zinc acetate stabilized by amphiphilic statistical copolymers, is prepared. By hydrolysis under basic conditions ZnO particles of a size below 100 nm are formed within the micelles. As the sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
89
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 144 publications
(90 citation statements)
references
References 34 publications
1
89
0
Order By: Relevance
“…12 Because of the special physical and chemical properties of the attached chemical species, devices based on ZnO NWs/NBs demonstrate unique and interesting properties. 13 In this paper, a layer-by-layer self-assembly method was used for manipulating and functionalizing polymers onto the surface of ZnO NBs. 14 In general, since the functional polymers used for UV sensing was negatively charged, a positively charged polymer, poly(diallyldimethylammonium chloride) (PDADMAC), was chosen to assist the electrostatic assembly of the negatively charged polymer.…”
Section: Performing Organization Name(s) and Address(es)mentioning
confidence: 99%
“…12 Because of the special physical and chemical properties of the attached chemical species, devices based on ZnO NWs/NBs demonstrate unique and interesting properties. 13 In this paper, a layer-by-layer self-assembly method was used for manipulating and functionalizing polymers onto the surface of ZnO NBs. 14 In general, since the functional polymers used for UV sensing was negatively charged, a positively charged polymer, poly(diallyldimethylammonium chloride) (PDADMAC), was chosen to assist the electrostatic assembly of the negatively charged polymer.…”
Section: Performing Organization Name(s) and Address(es)mentioning
confidence: 99%
“…ZnO has attracted intensive research effort for its unique properties and versatile applications in transparent electronics, chemical sensors, and spin electronics [2][3][4][5][6][7][8]. A variety of metal oxides like zinc oxide, titanium dioxide (TiO 2 ), and silicon dioxide (SiO 2 ) and different techniques such as chemical coprecipitation [9,10], sol-gel process [11,12] chemical vapour deposition [13], thermal decomposition [14,15], hydrothermal synthesis [16,17], solidstate reaction [18], spray pyrolysis [19], vapour-liquid-solid method [20], and microemulsion precipitation [21][22][23] have been used so far. Hingorani et al also reported the synthesis of ZnO nanoparticles (NPs) and it was the first study using reverse microemulsion in the early 1990s [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…The sol-gel method for the synthesis of inorganic nanoparticles such as ZnO, TiO 2 and SiO 2 [11][12][13][14][15] has become one of the most popular chemical procedures. The reason of this popularity stems from the fact that sol-gel synthesis is easy and it is carried out at ambient or slightly elevated temperature.…”
Section: Introductionmentioning
confidence: 99%